2018
DOI: 10.1590/1517-869220182401177117
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Physical Training Improves Fine Motor Skills of 5-Year-Old Children

Abstract: Introduction: Fine motor skills are important for children not only in the activities of daily living, but also for learning activities. In the present study, the effects of supervised physical training were investigated in normal children. Objective: To evaluate the effects of supervised training by combining full-body exercise and the eye-hand coordination activities to improve fine motor skills in a group of five-year-old normal children. Methods: Fifty-two children were selected and randomized in exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Physical training involving complete body exercise and hand grip strengthening exercises improved FMS of 5yearold normal children [26]. Increased HGS showed improvement in FMS not only in normal children but strength training was found to increase the muscle strength in general and HGS in persons with intellectual disabilities [27].…”
Section: Discussionmentioning
confidence: 90%
“…Physical training involving complete body exercise and hand grip strengthening exercises improved FMS of 5yearold normal children [26]. Increased HGS showed improvement in FMS not only in normal children but strength training was found to increase the muscle strength in general and HGS in persons with intellectual disabilities [27].…”
Section: Discussionmentioning
confidence: 90%
“…Such conclusions were reached by Lang et al assessing cardiorespiratory fitness with the 20 m shuttle run test 10 . Qi et al observed that after a 24-week training session, the group of studied children improved their motor skills (30-s speed tapping and throw a tennis ball) and hand grip strength, compared to the control group 11 . Leading an active lifestyle at this stage of life has also a positive effect on the child’s physical, cognitive and mental health 6 , 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Desse modo, os componentes da aprendizagem motora exercem influência significativa na aquisição das habilidades de aprendizagem cognitiva, como a consciência corporal, direcional e espacial, bem como sincronia, ritmo e sequência motora 6 . Diversos estudos apresentam a associação entre dificuldades motoras e déficits de aprendizagem 1,6,7 e evidenciam que déficits motores podem comprometer atividades cotidianas da criança 8 , prejudicar suas interações sociais e, consequentemente, comprometer sua autoestima e seu autoconceito 9,10 . Devido à importância das HM para o desenvolvimento físico, cognitivo, social e emocional do indivíduo 6 , surge a necessidade de estabelecer métodos adequados capazes de rastrear possíveis atrasos ou desordens do desenvolvimento.…”
Section: Introductionunclassified